Re-conceptualising student support in rapidly changing times - Michaels, L.; Lautenbach, G. (South African Journal of Higher Education, 2024)
It has been noted that without learning, there can be no success. Furthermore, at the most basic level, essential success implies successful learning in the classroom. This was the sentiment of Tinto and Pusser (2006, 8) two decades ago when the global turn to Emergency Remote Teaching and Learning was inconceivable. However, the Novel Coronavirus appeared in Wuhan, China at the end of 2019, and in 2020 the World Health Organisation announced COVID-19 as a global pandemic (Discovery 2020; WHO 2020) that caused major disruptions in all sectors of society and led to the unprecedented transition from the face-to-face mode of teaching and learning to online platforms in Higher Education Institutions (HEIs) worldwide (Turnbull, Chugh, and Luck 2021). It soon became clear to researchers that the support offered to students to assist them in attaining academic success had proven inadequate (Al-Maskari, Al-Riyami, and Kunjumuhammed 2022) and that the support systems used by HEIs needed to be revisited. This article examines student best practices during the COVID-19 pandemic and beyond to ensure that students enjoy optimal benefits as they strive for academic success. The article further suggests a student support theory that can be employed by HEIs to better assist students in the quest for attaining a postgraduate qualification.